Trends in myopia development among Chinese children and adolescents in Xuzhou during one academic year - Li, Lin; Liao, Ya; Wang, Qian; Wang, Mei; Zhang, Wenxuan; Wang, Xiaojuan (Frontiers in Medicine, 2024)
Purpose This study investigates the prevalence and progression of myopia among primary and secondary school students in Xuzhou City, China, during one academic year. Methods The study employed a prospective research design and utilized a whole-group sampling method to conduct non-cycloplegic spot photo screenings on 37,938 students from 44 primary and secondary schools in Xuzhou City, China. A one-year study was conducted to gather spherical equivalent refraction (SER), and subsequent analysis was carried out to explore the disparities in myopia prevalence among primary and secondary school students within the same academic year, as well as the progression of myopia. Results During the 2022 academic year, the overall prevalence of myopia in the first and second semesters was 62.6 and 64.2% respectively, indicating an increasing trend. Particularly in primary school (Grades 1–6), the prevalence of myopia increased with higher grade levels, and significant variations in myopia prevalence were observed mainly in grades 1–3 and 7 (p < 0.05). The incidence rate of myopia in middle school remained stable, while in primary school, there was a positive correlation between myopia incidence and the grade level, with the highest rate of 20.1% in grade 6. Among the myopic population, the median value of spherical equivalent refraction slightly decreased between the two semesters. The proportion of high myopia increased among students in grades 5–8. Conclusion Our study revealed that within one academic year, the prevalence of myopia and the severity of myopia have significantly increased in Xuzhou City, China, accompanied by an increase in the proportion of high myopia. For different grade levels, we should adopt personalized prevention and control measures, with a particular focus on lower grade levels and students who have just entered a new grade.